Moving together to drive the nation’s technical capability - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) staff must all move together so as to boost the nation’s technical capability and enrich the field of technical, vocational, education and training (TVET), in line with the needs of the high-tech industries.